Money, Banking and Financial Markets in Central and Eastern Europe 2010
DOI: 10.1057/9780230302211_4
|View full text |Cite
|
Sign up to set email alerts
|

Financing Constraints, Credit, Rationing, and Financing Obstacles: Evidence from Firm Level Data in South Eastern Europe

Abstract: Financing constraints have been one of the major impediments to doing business in transition economies in general and SouthEastern Europe in particular. Utilizing firm-level survey data and extensive econometric modelling, the paper provides new evidence on financing constraints, credit rationing and financing obstacles for firms in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
2
14
1
3
Order By: Relevance
“…Hashi and Krasniqi (2011), employing ordinary least squares (OLS) regression and using data from the Business Environment and Enterprise Survey (BEEPS) in cases of three Central European (Poland, Hungary, Czech Republic) and three SEE countries (Albania, Macedonia, Serbia, and Montenegro), argued that differences in access to external financing between country groups were related to the growth stages of SMEs and levels of institutional development. Hashi and Toçi (2010), applying the tobit and logit models to BEEPS data, examined firm-specific determinants of SMEs' financing constraints in SEE. The authors concluded that compared with large firms, SMEs are more financially constrained, relying mostly on internal financial sources because their loan applications are more likely to be refused.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hashi and Krasniqi (2011), employing ordinary least squares (OLS) regression and using data from the Business Environment and Enterprise Survey (BEEPS) in cases of three Central European (Poland, Hungary, Czech Republic) and three SEE countries (Albania, Macedonia, Serbia, and Montenegro), argued that differences in access to external financing between country groups were related to the growth stages of SMEs and levels of institutional development. Hashi and Toçi (2010), applying the tobit and logit models to BEEPS data, examined firm-specific determinants of SMEs' financing constraints in SEE. The authors concluded that compared with large firms, SMEs are more financially constrained, relying mostly on internal financial sources because their loan applications are more likely to be refused.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In keeping with the literature (Barth et al, 2011;Hashi & Toçi, 2010), financial constraint was measured based on the responses of firms' managers to the question, "Is access to finance, which includes its availability and cost, interest rates, fees, and collateral requirements, an obstacle to the operation of this establishment," which ranged from 0 (no obstacle) to 4 (very severe obstacle).…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…Toci & Hashi, 2010;Stephanou & Rodriguez, 2008;Mambula, 2002;Okpara & Wynn, 2007) in finding that high interest rates are statistically significant to SMEs' financing obstacles. Because of measurement variance, the results of this study are inconsistent with previous studies (Gray et al, 1997;Kiggundu, 2002;Trulsson, 1997;vanDijk, 1995;Toci & Hashi, 2010;Stephanou & Rodriguez; which indicate that most SMEs cannot meet the requirements for commercial loans because they lack sufficient collateral. The finding that favourable interest rates explain significant variances in access to formal credit indicates that lending institutions in Uganda offer loans at unfavourable interest rates.…”
Section: [Insert Table III About Here]mentioning
confidence: 99%
“…The evidence shows that better access to external finance is likely to be one of the most effective routes to promoting firm growth (Pissarides 1999;Filatotchev and Mickiewicz 2006;Hashi and Toci 2010;Wehinger 2014).…”
Section: Business Environment Literature Reviewmentioning
confidence: 99%